Comprehensive repair for girls, boys and adolescents victims of physical and sexual abuse in Ecuador - Ronquillo Numerable, Leonel Efraín (Revista Universidad de Guayaquil, 2025)
The issue related to children's rights has become an essential aspect of global legislation, especially in Latin American countries such as Ecuador, where the levels of violence against this social group have worsened in recent years. Thus, the main objective of this scientific article was to analyze the relevance of comprehensive reparation for girls, boys and adolescents who have been victims of physical and sexual abuse in Ecuador. To achieve this objective, a descriptive methodology was applied, under a qualitative and legal-doctrinal approach, through the use of the analytical method and the content analysis technique. The results achieved allowed us to verify that the regulatory framework in Ecuador certainly has special provisions in this area to guarantee the rights of minors, however, in reality, when trying to impose legislative actions, their application is limited by insufficient resources, poor coordination between the different institutions involved and a culture that tends to deepen violence against minors. It was concluded that the lack of effective solutions that promote comprehensive reparation for victims and their families continues to be a major problem in Ecuadorian society, which is why it should not only include economic compensation, but also strengthen actions that promote the physical, emotional and social recovery of minors who experience this type of situation.
Keywords: Gender violence; human rights; Protection of victims; Prevention of violence.